An Investigation into the Translation Hyperboles from Vietnamese into English as Manifested in English Versions of Truyện Kiều - Hoàng Trương Phước Lộc (2011)
Being a stylistic device having a great power of expressive meaning, hyperbole is utilized wonderfully by Nguyễn Du to compose a lot of beautiful verses that contribute to make Truyện Kiều into a masterpiece. Arising from ….